Gene pool transmission of multidrug resistance among Campylobacter from livestock, sewage and human disease. (27th August 2019) - Mourkas, Evangelos; Florez‐Cuadrado, Diego; Pascoe, Ben; Calland, Jessica K.; Bayliss, Sion C.; Mageiros, Leonardos; Méric, Guillaume; Hitchings, Matthew D.; Quesada, Alberto; Porrero, Concepción; Ugarte‐Ruiz, María; Gutiérrez‐Fernández, José; et al.
Summary: The use of antimicrobials in human and veterinary medicine has coincided with a rise in antimicrobial resistance (AMR) in the food‐borne pathogens Campylobacter jejuni and Campylobacter coli . Faecal contamination from the main reservoir hosts (livestock, especially poultry) is the principal route of human infection but little is known about the spread of AMR among source and sink populations. In particular, questions remain about how Campylobacter resistomes interact between species and hosts, and the potential role of sewage as a conduit for the spread of AMR. Here, we investigate the genomic variation associated with AMR in 168 C. jejuni and 92 C. coli strains isolated from humans, livestock and urban effluents in Spain. AMR was tested in vitro and isolate genomes were sequenced and screened for putative AMR genes and alleles. Genes associated with resistance to multiple drug classes were observed in both species and were commonly present in multidrug‐resistant genomic islands (GIs), often located on plasmids or mobile elements. In many cases, these loci had alleles that were shared among C. jejuni and C. coli consistent with horizontal transfer. Our results suggest that specific antibiotic resistance genes have spread among Campylobacter isolated from humans, animals and the environment.